EFEK EKSTRAK ETANOL DAUN GEDI MERAH (Abelmoschus manihot L.) TERHADAP GAMBARAN HISTOLOGI GINJAL TIKUS PUTIH JANTAN (Rattus norvegicus) MODEL UROLITHIASIS - Irma Santi; Rahmawati Rahmawati; Lili Tari (JOURNAL OF PHARMACY SCIENCE AND TECHNOLOGY, 2021)
Urolithiasis or kidney stones is a disease caused by urine sediment in the urinary tract. It can be observed histologically by investigating the presence of crystals and tissue damage such as degeneration hydropis, hemorrhage, and necrosis. The aim of this reseach is to prove the effect of ethanol extract of red gedi leaves (Abelmoschus manihot L) on histological of white rat kidney (Rattus norvegicus) urolithiasis model. This reseach used 15 rat devided into 5 groups. Group 1 was the normal group; group 2 was induced by ethylene glycol 0,75% and ammonium chloride 1 %; group 3,4 and 5 were a test group induced by ammonium chloride 1 %; group 3,4 and 5 were a test ammonium chloride 0.75 % and 1 % and ethanol extract of red gedi leaves with succesive doses of 10 mg/kgBW, 20 mg/kgBW, 40 mg/kgBW. The data were analyzed statistically using Kruskal wallis test and Mann-Whitney’s advanced test. The result showed that the group of red gedi leaf extract with doses 40 mg/kgBW statically has the best effect as antiurolithiasis on the white rats. As conclusion, extract of red gedi leaves can be used to urolithiasis.